Azilsartan Medoxomil and Cilnidipine Spectrophotometric Determination in Bulk and Formulation: A Validated Dual Wavelength Method - M. S, Siddalinga Swamy; Sarsambi, Prakash S; M P, Lavanya Patil; M, Shwetha; B M, Santhosh (Indian Journal of Pharmaceutical Education and Research)
Introduction: If there is a rise in blood pressure then that condition is called hypertension. Azilsartan medoxomil and Cilnidipine is a new combined dosage form used in the treatment of Stage II Hypertension. Objectives: The main intention of the research is to reinforce a validated dual wavelength spectrophotometric approach for the combined evaluation of AZL and CIL in bulk and formulation. Materials and Methods: In the dual wavelength approach, for each drug two wavelengths have been chosen such that they exhibit the same absorbance or the difference in absorbance for each drug is 0. Two wavelengths 229.5 nm and 256.5 nm opted for the detection of AZL while CIL exhibits the same absorbance. Similarly, 238 nm and 258 nm opted to determine CIL while AZL exhibits the same absorbance at both of these wavelengths. The solvent employed was ethanol. Results: Linearity lay between the quantitation range of 1-5 μg/mL for AZL and 4-20 μg/mL for CIL. LOD and LOQ for AZL and CIL were revealed to be 0.6278 μg/mL and 0.0931 μg/ mL and 1.9026 μg/mL and 0.2821 μg/mL respectively. The calculated % recovery was found to be 99.97±0.45 for AZL whereas 100.15±0.035 for CIL. Conclusion: The validated method was found to be simple, sensitive, easy and affordable for a quantitative estimate of AZL and CIL. Through the use of ICH criteria, the method was validated.
Keywords: Azilsartan medoxomil; Cilnidipine; Dual Wavelength Method; Hypertension.